Exploring Traditional Game Congklak as an Effective Learning Tools for Elementary Schools - Ayuningrum, Haliza; Fauziyah, Siti Nur; Fauziah, Farahatul; Juhji (Tarunateach: Journal of Elementary School, 2024)
The traditional game of congklak has become the focus of research as a learning medium in elementary schools. This study aims to evaluate the effectiveness of congklak as an educational tool and identify its potential educational benefits. The research method used is a literature study, collecting several previous studies to assess the effectiveness of the traditional game of congklak as a learning medium. The results show that congklak is effective in increasing students' interest in learning mathematics and their social skills in elementary schools. The traditional game of congklak as a learning medium is favored by students. This is evident from the results of previous studies, which show that students' responses are very positive toward the use of the traditional game of congklak as a learning medium in elementary schools.